2006
DOI: 10.1111/j.1601-183x.2006.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired spatial learning in the APPSwe + PSEN1ΔE9 bigenic mouse model of Alzheimer’s disease

Abstract: Mice co-expressing the Swedish amyloid precursor protein mutation (APP Swe ) and exon 9 deletion (DE9) of the PSEN1 gene begin to develop amyloid plaques at 6-7 months of age. We demonstrate here a spatial learning deficit in 7-month-old APP Swe + PSEN1DE9 bigenic mice using an adaptation of the Barnes maze. Mice were first trained on a cued target followed by a hidden-target condition. Although bigenic mice quickly learned the cued-target version of the task, they were significantly impaired when switched to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
276
3
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(312 citation statements)
references
References 41 publications
(39 reference statements)
32
276
3
1
Order By: Relevance
“…Previous studies report that APP/PS1 mice show reference memory impairments by 3 months of age and persist throughout life (Reiserer et al 2007;Bernardo et al 2009;O'Leary and Brown 2009). By comparing these results with our previous Y-maze test for behavioral analysis of 11-12-month-old APP/PS1 mice , we found that 24-month-old APP/PS1 cohorts show more severe working and reference memory impairment.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies report that APP/PS1 mice show reference memory impairments by 3 months of age and persist throughout life (Reiserer et al 2007;Bernardo et al 2009;O'Leary and Brown 2009). By comparing these results with our previous Y-maze test for behavioral analysis of 11-12-month-old APP/PS1 mice , we found that 24-month-old APP/PS1 cohorts show more severe working and reference memory impairment.…”
Section: Discussionsupporting
confidence: 60%
“…These observations are consistent with a previous study showing obvious thigmotactic behavior in 7‐month‐old APP/PS1 mice of the same strain (Ferguson et al ., 2013). However, the anxiety levels of these transgenic mice are inconsistent among different studies, and it seems that anxiety‐related behaviors are task‐specific (Lalonde et al ., 2004; Reiserer et al ., 2007). Other anxiety‐related tests such as light–dark test and elevated plus maze are needed to validate the anxiety level of these mice and the anxiolytic effect of intranasal insulin in these mice.…”
Section: Discussionmentioning
confidence: 99%
“…APP/ PS double-transgenic mice coexpress a chimeric mouse/ human APP Swedish mutant (APPswe) and a mutant human PS1 (PS1ΔE9) [52]. These transgenic mice display an aggressive onset of age-dependent neuritic Aβ deposition in the cortex and hippocampus, and begin to show memory deficits at the age of 6 months [53,54]. Drug administration began prophylactically at 4 months of age (that is, about 2 months before the onset of phenotype).…”
Section: Antagonization Of Dor By Nti Mitigates Ad-like Pathology In mentioning
confidence: 99%